2014
DOI: 10.3892/ol.2014.2136
|View full text |Cite
|
Sign up to set email alerts
|

Preventive effects of the angiotensin-converting enzyme inhibitor, captopril, on the development of azoxymethane-induced colonic preneoplastic lesions in diabetic and hypertensive rats

Abstract: Metabolic syndrome (Mets), including diabetes and hypertension, increases the risk of colorectal cancer via the induction of chronic inflammation, acceleration of oxidative stress, and activation of the renin-angiotensin system. The present study examined the possible inhibitory effects of captopril, an angiotensin-converting enzyme (ACE) inhibitor and antihypertensive drug, on the development of azoxymethane (AOM)-induced colonic premalignant lesions, aberrant crypt foci (ACF), in SHRSP.Z-Leprfa/IzmDmcr (SHRS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Four compounds are FN, i.e., a DA 1 /α 1 agonist ( 232 ) that induced pancreatic acinar cell adenoma, an imidazole PDE inhibitor ( 216 ) that was associated with adrenal pheochromocytomas, a quinolone vasodilator ( 225 ), and a renin inhibitor ( 198 ) that was associated with colon adenoma and carcinoma. However, the colon is unlikely to be a pharmacological target, as Kochi et al ( 43 ) described an antagonistic effect for this relation. Therefore, we decided to give a TN category to this class.…”
Section: Resultsmentioning
confidence: 99%
“…Four compounds are FN, i.e., a DA 1 /α 1 agonist ( 232 ) that induced pancreatic acinar cell adenoma, an imidazole PDE inhibitor ( 216 ) that was associated with adrenal pheochromocytomas, a quinolone vasodilator ( 225 ), and a renin inhibitor ( 198 ) that was associated with colon adenoma and carcinoma. However, the colon is unlikely to be a pharmacological target, as Kochi et al ( 43 ) described an antagonistic effect for this relation. Therefore, we decided to give a TN category to this class.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, recent studies have demonstrated that certain types of phytochemicals such as curcumin and (−)-epigallocatechin gallate inhibit the development of obesity-related colorectal carcinogenesis in mice by attenuating chronic inflammation [ 11 , 12 ]. Administration of angiotensin-converting enzyme inhibitor also suppresses the early phase of colorectal carcinogenesis in diabetic and hypertensive rats by attenuating inflammation and oxidative stress [ 13 ]. These reports suggest that targeting obesity-related metabolic abnormalities including chronic inflammation and oxidative stress using phytochemicals and specific agents is an effective strategy for preventing CRC development in obese individuals [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our results suggest that attenuation of oxidative stress might be essential for suppressing both DSS-induced colonic inflammation and AOM/DSS-induced colon carcinogenesis. Previous research has also demonstrated that decreased oxidative stress significantly suppressed colorectal tumourigenesis in rodent models [29][30][31] . Intestinal barrier function is also associated with inflammation and affects the intestinal condition.…”
Section: Discussionmentioning
confidence: 88%